Google+
Facebook
LinkedIn
Twitter
Digg
StumbleUpon
Home
Download PDF
Order CD-ROM
Order in Print
Factoring Quadratic Equations - h1014v1_135
Factoring Quadratic Equations - h1014v1_137
Mathematics Volume 1 of 2
Page Navigation
108
109
110
111
112
113
114
115
116
117
118
QUADRATIC EQUATIONS
Algebra
Example:
Solve the following quadratic equation by factoring.
2
x
2
- 3 = 4
x
-
x
2
+ 1
Solution:
Step 1.
Using the subtraction axiom, subtract (4
x
-
x
2
+ 1) from both sides of the
equation.
2
x
2
- 3 - (4
x
-
x
2
+ 1) = 4
x
-
x
2
+ 1 - (4
x
-
x
2
+ 1)
3
x
2
- 4
x
- 4 = 0
Step 2.
Factor the resulting equation.
3
x
2
- 4
x
- 4 = 0
(3
x
+ 2)(
x
- 2) = 0
Step 3.
Set each factor equal to zero and solve the resulting equations.
3
x
+ 2 = 0
3
x
= -2
3
x
3
2
3
x
=
2
3
x
- 2 = 0
x
= 2
Thus, the roots are
x
=
and
x
= 2.
2
3
MA-02
Page 22
Rev. 0
Integrated Publishing, Inc. - A (SDVOSB) Service Disabled Veteran Owned Small Business